The Effect of Easy and Quality Service on Interest in Using BCA Mobile Banking through Trust as an Intervening Variable - Angga Putri Ekanova Nurlaela; Septi Mariani Tis’a Ramadhani; Yunita Niken Ayu Ramadhanti (Yayasan Ilomata, 2023)
The rapid development of science and technology in the digital era has influenced people's lifestyles when accessing a lot of information in various service functions via electronic means. Banking utilizes information technology in mobile banking services. The aim of this research is to determine and analyze the influence of perceived convenience and service quality on interest in using BCA Mobile Banking through trust as an intervening variable. The research method uses primary data obtained from distributing questionnaires to 100 people aged at least 17 years who have used or are currently using BCA Mobile Banking in Jabodetabek. The analytical tools used are validity test, reliability test, R-Square test, path coefficient test, and indirect effect test (path analysis). The research results show that perceptions of convenience and service quality influence interest in using BCA Mobile Banking through trust. Perceived convenience does not influence interest in using BCA Mobile Banking, while service quality influences interest in using BCA Mobile Banking. Perception of Ease and Quality of Service directly and indirectly influences Interest in Using BCA Mobile Banking through Trust